(untitled) (Scientific journal of the Fergana State University, 2023)
The intellectual potential of young people occupies an important place in the system of community potential. From the perspective of development, the importance of the intellectual potential of young people as the main force that determines the essence of future history is revealed. Certain social and cultural factors are analyzed on the basis of its existence and development. It has been studied that factors such as the high level of human potential in society, its characteristics and the realization of a number of social events related to this problem affect the development of any state, nation and the social development of the country’s life.